Estimating the Intangible Victim Costs of Violent Crime - Dolan, Paul; Loomes, Graham; Peasgood, Tessa; Tsuchiya, Aki (The British journal of criminology, 2005)
Current estimates of the intangible costs of violent crime, such as the pain, grief and suffering experienced by victims, are not very robust. This paper sets out the different methods that can be used to provide more defensible cost estimates, and that use data that are currently available. One of these methods involves estimating the number of quality-adjusted life years (QALYs) that victims of crime lose. The estimates suggest that rape results in the biggest losses, followed (in descending order) by: other wounding, common assault, serious wounding, murder, robbery and sexual assault